Effect of zeolite synthesized from rice husk silica towards mixed matrix polysulfone ultrafiltration membrane - Rosman, Nurafiqah (Universiti Teknologi Malaysia, 2014)
In the present work, polysulfone (PSf) ultrafiltration membranes were prepared by solution casting via phase inversion process. The effects of synthesized rice husk (RH) zeolite on the properties and performance of the casted PSf membrane were observed and investigated. Characterization of synthesized RH zeolite and morphology of membrane were conducted by using X-ray diffractometer (XRD), field emission microscopy (FESEM) and scanning electron microscopy (SEM). XRD analysis shows a mixture of zeolite A, Y and P, while FESEM images showed agglomeration of cubic-shaped morphology of the synthesized RH zeolite. SEM analysis on membrane morphology indicates that the addition of synthesized RH zeolite obviously changed the microstructure of the membrane sub layer. At 2g RHY content, the membranes held the highest water permeability (315.29 Lm-2h-1) and continuously decreased with higher RHY content. The incorporation of the RHY particles beyond 2% causes declination to the membrane flux and increment to the humic acid rejection from 95.8 to 99.6%.